Antara prohibisi dan legitimasi: Analisis Komparatif Hukum Berjabat Tangan dengan Lawan Jenis dalam Pandangan Ulama - Suhaeri, Suhaeri (Sharia Journal and Education Center Publishing, 2026)
The practice of handshaking between men and women who are not mahram (permissible marriage partners) remains a controversial issue among Muslims, especially when religious norms intersect with modern cultural and professional expectations. Divergent scholarly opinions on this issue reflect a broader tension between classical fiqh textualism and contemporary contextual reasoning. Scholars from schools such as Shafi’i and Hanbali generally prohibit it absolutely, while Hanafi scholars and some contemporary figures like Yusuf al-Qaradawi allow it under specific conditions, emphasizing intention and social context. This study investigates how classical and modern scholars interpret the ruling on handshaking with the opposite sex and how the maqāṣid al-sharīʿah framework can be used to assess the relevance and applicability of these rulings in today’s pluralistic societies. Employing a qualitative method through library research and comparative analysis, this study highlights the importance of integrating Islamic legal principles with contemporary social realities. This study concludes that the stronger opinion is the opinion that it is permissible, as long as it is not accompanied by lust and does not give rise to slander.